“You eat, but you never have enough …”: fear of famine and food shortage in the Hebrew Bible and the Ancient Near East - Kipfer, Sara (Die Welt des Orients, 2021)
Famine belongs to one of several divine punishments which are referred to again and again in the Hebrew Bible and throughout the Ancient Near East. Oracles and curses mention famine as a future-conditional event. This paper focuses on a subgroup of texts announcing not only famine and aggregate food-supply shortfalls but expressing the abolition of the regular order and the connection between deed and punishment (e. g., people will plant but never enjoy the fruits, they will eat but never have enough, etc.). While in the so called indictment/judgment oracles (e. g. Hos 4:10-11; Am 4:6-8; 5,10-11; Mic 6:9-16; Zeph 1:12-13) the offence has already be done, in the so called “treaty curses” the punishment will only be fulfilled in case of violation of the inscription (Statue from Tell Feḫerīye; Bukān Stela), the treaty (Sfīre Stela) or the covenant (Lev 26:14-39; Deut 28:15-44). In either case the emotion of fear plays an important part. These dystopian texts (“futility curses”) convey a warning predicting a bleak future and in some cases the expectation of the future even surpasses what has been experienced in the past by stressing the futility of action.